2009
DOI: 10.1242/jeb.023531
|View full text |Cite
|
Sign up to set email alerts
|

Decreased precision contributes to the hypoxic thermoregulatory response in lizards

Abstract: SUMMARYThe decrease in body temperature (T b ) observed in most vertebrate classes in response to hypoxia has been attributed to a regulated decrease in set-point, protecting organs against tissue death due to oxygen depletion. Hypoxia, however, imparts particular challenges to metabolic function which may, in turn, affect thermoregulation. In ectotherms, where thermoregulation is mainly behavioural, stressors that influence the propensity to move and respond to temperature gradients are expected to have an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…±2°C from the PT) support the notion that crayfish actively select and defend a temperature (Bückle Ramirez et al, 1994;Casterlin and Reynolds, 1977;Casterlin and Reynolds, 1980;Crawshaw, 1974;Payette and McGaw, 2003;Taylor, 1984;Taylor, 1990). Furthermore, crayfish required to thermoregulate are far more active than those that are held at a constant temperature, indicating that temperature selection is a strong motivating factor (Cadena and Tattersall, 2009a;Cadena and Tattersall, 2009b). Indeed, previous research has demonstrated that the crayfish Orconectes immunis will also raise their thermal preference upon infection, by as little as 1°C (Casterlin and Reynolds, 1977).…”
Section: Thermoregulation In Crayfishsupporting
confidence: 59%
See 1 more Smart Citation
“…±2°C from the PT) support the notion that crayfish actively select and defend a temperature (Bückle Ramirez et al, 1994;Casterlin and Reynolds, 1977;Casterlin and Reynolds, 1980;Crawshaw, 1974;Payette and McGaw, 2003;Taylor, 1984;Taylor, 1990). Furthermore, crayfish required to thermoregulate are far more active than those that are held at a constant temperature, indicating that temperature selection is a strong motivating factor (Cadena and Tattersall, 2009a;Cadena and Tattersall, 2009b). Indeed, previous research has demonstrated that the crayfish Orconectes immunis will also raise their thermal preference upon infection, by as little as 1°C (Casterlin and Reynolds, 1977).…”
Section: Thermoregulation In Crayfishsupporting
confidence: 59%
“…To establish the duration of time required for crayfish to become accustomed to the experimental chamber and reduce its exploratory activity to a consistent level (Cadena and Tattersall, 2009a;Cadena and Tattersall, 2009b), a 'habituation' experiment was performed (N10 individuals). This experiment was also used to determine whether a side preference or bias existed in the test tank.…”
Section: Experimental Procedures Series I: Habituation and Side Bias mentioning
confidence: 99%
“…Before each experiment, lizards were placed in a small incubator (Exo-Terra Thermoelectric Egg Incubator, Rolf C. Hagen Corp., Mansfield, MA, USA) at a temperature of 35°C for a minimum of 45 min to allow for thermal equilibrium at the bearded dragon's preferred body temperature (Cadena and Tattersall, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…In both seasons, the selected T a was lower in hypoxia, in parallel with the decrease in T b . Interestingly the fluctuations in T b were greater in hypoxia than normoxia (Table 3) and might be attributed to a hypoxiainduced decrease in thermosensation and thermoregulatory precision (Cadena and Tattersall, 2009).…”
Section: Hypoxic Thermoregulatory Response In Eastern Chipmunksmentioning
confidence: 97%